GC-MS Analysis of Methanolic Extract of Gyrocarpus asiaticus Willd - Kanta Kanthal, Lakshmi; Dey, Akalanka; Satyavathi, K.; Bhojaraju, P. (Asian Journal of Chemistry, 2015)
The present study was designed to determine the bio-active compounds in the aerial parts of the methanolic extract of Gyrocarpus asiaticus Willd. GC-MS analysis of the aerial parts of the methanolic extract of Gyrocarpus asiaticus Willd was performed on a GC-MS equipment (Thermo Scientific Co. Thermo GC-TRACE ultra ver.: 5.0, Thermo MS DSQ II). The preliminary phytochemical tests showed the presence of alkaloids, cardiac glycosides, flavonoids, phenols, saponins, steroids, tannins and terpenoids in methanolic extract of Gyrocarpus asiaticus Willd. The GC-MS analysis has shown the presence of fifteen different phytochemical compounds in the methanolic extract of Gyrocarpus asiaticus Willd. From the results, it is evident that Gyrocarpus asiaticus Willd contains various phytocomponents and is recommended as a plant of great phytopharmaceutical importance.